The Necessity to Observe the Interests of the company in the Assumption of Director’s Contract with Himself with Recognition in the British Legal System - Hosein Bahrami (پژوهشهای حقوقی)
The manager's transaction on behalf of the company with himself is a situation of conflict of interest and is possible that the manager considers his own interests to be preferable to the interests of it; Accordingly, the legislator should try to protect the company. The legislator has issued a ruling only in relation to a joint-stock company what he means is the place of dispute; Therefore, the purpose is to deduce the legislator's opinions regarding the mentioned company and others in comparison with English law. In the above company, managers must first take the consent of the board of directors and then the general meeting of co-partners (Article 129 of the Amendment bill of the commercial code). Otherwise, the transaction can be canceled; even if invalidity conflicts with third-party rights with good intentions (Article 131 of the mentioned code); However, if the consent of the board of directors has been obtained and the assembly does not approve, and the invalidity of the transaction conflicts with the third party, the transaction will be valid with respect to him (Article 130 of the above code). In other companies, according to the similarity, the same rulings should be valid; As for the cooperative society, the rules of the joint stock company are current; but sometimes, it is not possible; Therefore, the rules of agency must be enforced. In the British, the above transaction is also accepted; But it has differences with Iran; Such as all companies are subject to uniform rules.